2021
DOI: 10.1007/s12662-021-00730-w
|View full text |Cite
|
Sign up to set email alerts
|

Leisure time sports and exercise activities during the COVID-19 pandemic: a survey of working parents

Abstract: Many working parents experienced a double burden of fulltime employment and increased childcare obligations during the COVID-19 (coronavirus disease 2019) pandemic. This paper explores how this twofold burden affected leisure time sports and exercise (LTSE). Following a gender inequality perspective, it is assumed that the level of LTSE of working mothers are more negatively affected by the pandemic than LTSE levels of working fathers. Using the nation-wide representative SPOVID survey, the paper analyses data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
3
12
2
Order By: Relevance
“…Second, we found that in general the frequency of participation of men showed a steeper decline than that of women. This is contrary to many other studies that have found that women and girls participation and health declined more under COVID-19 than that of boys and men [ 14 , 24 , 25 ]. This is reportedly due to the additional impact on women of the care burden of children, home schooling, and looking after sick family members, and of women being more impacted by job losses [ 14 , 24 , 25 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Second, we found that in general the frequency of participation of men showed a steeper decline than that of women. This is contrary to many other studies that have found that women and girls participation and health declined more under COVID-19 than that of boys and men [ 14 , 24 , 25 ]. This is reportedly due to the additional impact on women of the care burden of children, home schooling, and looking after sick family members, and of women being more impacted by job losses [ 14 , 24 , 25 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This is contrary to many other studies that have found that women and girls participation and health declined more under COVID-19 than that of boys and men [ 14 , 24 , 25 ]. This is reportedly due to the additional impact on women of the care burden of children, home schooling, and looking after sick family members, and of women being more impacted by job losses [ 14 , 24 , 25 ]. However, there is also other evidence that individuals who were active within sports clubs were less likely to exercise during COVID-19 restrictions [ 26 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…First, pandemic influence and leisure environment have a positive effect on leisure satisfaction. Such relationships have been observed in previous studies, which have confirmed that the pandemic indirectly improved leisure satisfaction by making people more attentive to and engaged in leisure activities [ 29 ]. Additionally, Li et al [ 63 ] suggested that a sense of community is positively associated with street greenery at the community level.…”
Section: Discussionsupporting
confidence: 83%
“…After the COVID-19 outbreak, urban community residents began to pay much more attention to the different elements of leisure, such as leisure time, leisure activities, and leisure environments [ 28 ]. During the pandemic, leisure activities, especially sports and exercise activities, were associated with positive emotions and high levels of life satisfaction, in addition to good physical health [ 29 ]. Therefore, the pandemic influence may play a positive role in leisure satisfaction through a particular mechanism.…”
Section: Literature Review Conceptual Framework and Hypothesesmentioning
confidence: 99%